Risks and adaptation strategies in rainfed agriculture in India: An analysis - PRAVEEN, K V; SURESH, A; REDDY, A A; SINGH, D R (The Indian Journal of Agricultural Sciences, 2018)
Farmers in the rainfed regions of India have to routinely deal with risks from biotic and abiotic sources, that varies with the region and crop cultivated. An assessment of the risk sources and adaptation strategies is attempted in this paper using a total of 500 farmers combinedly from Maharashtra and Telangana. Data collected using a questionnaire in Likert scale format was analysed using principal component factor analysis. With regard to the willingness to take risk by the farmers, just below half of the farmers were risk averse. Issues faced by the farmers with regard to inputs, private information sources, public information sources, irrigation, non-institutional credit sources, custom hiring services, and institutional credit sources were perceived as major risk sources. Strategies perceived by farmers as important to adapt to the risk situations were identified as the ones related to varietal management, community support, price stabilisation mechanism, government support, and self-insurance.